Researching and teaching social issues : the personal stories and pedagogical efforts of professors of education - Totten, Samuel; Pedersen, Jon E., 1960- (Emerald Publishing Limited : Information Age Publishing, 2012)
(orginally published by Lexington Books, A division of Rowman & Littlefield)Researching and Teaching Social Issues: The Personal Stories and Pedagogical Efforts of Professors of Education is comprised of original personal essays in which notable teacher educators delineate the genesis and evolution of their thought and work vis-a-vis the teaching of social issues. In relating their personal stories, the authors were asked to discuss among other issues those individuals and/or scholarly works that have most influenced them and how, their own aspirations in the field, the frustrations they have faced, their perceptions of the field, their major contributions, and their current endeavors. Our goal was that each and every story be as informative, instructive, and engaging as possible. We believe that readers will be thoroughly engaged as they read the stories of these individuals--stories that are inspiring, filled with passion, and reflective in nature. We also believe that readers will gain unique pedagogical insights into the field and ample food for thought.The individuals selected for inclusion in the book dedicated a great amount of time, thought, energy, and commitment to creating powerful and pedagogically sound ways to teach about social and/or controversial issues. Many have done so for well over forty years, and have been among the strongest advocates vis-à-vis the place social issues have in the extant curriculum and beyond.